Overview of the 22-year history of the Korea Coaching Development Center (KCDC) - Park, J.-K. (International Journal of Coaching Science, 2020)
A coach is a very important person who influences players' performance in sports situations. Coaching is also a major factor in improving players' performance. In this sense, the author recognized the importance of coaches and coaching in advance and made efforts to create coachingrelated organizations, which resulted in the creation of the current Korea Coaching Development Center. The purpose of this study was to introduce the history of KCDC and 12 thematic projects and activities that KCDC has been working on since its founding on November 7, 1998 and reexamine the past and future of sports coaching and make a new leap forward in the field of sports coaching. Based on the existing four research and oral presentation papers (Park, 2007, 2008, 2018, and 2019) related to KCDC history, this article gives an overview of these papers. KCDC websites (www.ikcdc.net, www.isgkorea.com), Journal of Coaching Development, International Journal of Coaching Science, and related data were used as measurement tools for 22 years. Details of the measuring tools are below. Data were analyzed by categorizing many activities into similar activities or projects for 22 years. The KCDC had worked a lot of projects and activities for 22 years so that 12 extensive projects and activities were categorized. The highlights of the Center's projects and activities include: publications, academic seminar, Graduate School, private qualifications training, training programs, Regional Coaching Development Center, CDC Successful Coach Awards, coaching clinic & academy, international exchange, financial support, industry-academic-research center-government cooperation, and cooperation with International Sports Group (ISG). The KCDC plans to continue its strong work in order to fulfill its objectives. Therefore, KCDC and ISG aim to be a global coaching research/education/business institute, to contribute to the globalization of sports coaching by global human networks, to nurture global coaching leaders for the era of fusion and convergence, and to contribute to global sport industry by forming strategic alliances with KCDC and ISG.